Effectiveness of a double-carbapenem combinations against carbapenem-resistant Gram-negative bacteria - Jiayue Lu; Yan Qing; Ning Dong; Congcong Liu; Yu Zeng; Qiaoling Sun; Qiao Shentu; Lixing Huang; Yingqian Wu; Hongwei Zhou; Zhangqi Shen; Rong Zhang (Elsevier, 2022)
The emergence of carbapenem-resistant organisms posed considerable threat to global health while only limited treatment options are available and led to efforts to discover a novel way to treat them. To evaluate in vitro synergistic activity of meropenem plus ertapenem, a total of 203 carbapenem-resistant strains, collected from 12 provinces and municipalities in China, were examined with a dual carbapenem combination therapy. The statistical software R was used for analysis. Two hundred and one (201) of carbapenem-resistant strains mainly produced four types of carbapenemase: KPC-2 (n = 142, 69.95%), OXA-232 (n = 7, 3.45%), NDM (n = 38, 18.72%; 36 NDM-1, 1 NDM-4, 1 NDM-5), and IMP (n = 15, 7.39%; 1 IMP-26, 10 IMP-30, 4 IMP-4). Fifty-one out of two hundred and three (51/203 or 25.12%) of the examined strains showed a synergistic effect for the meropenem plus ertapenem combination throughout the checkerboard method, while only three isolates showed potential clinically relevant synergy (3/203, 1.48%). An additive effect was observed in 55/203 (27.09%) of the examined strains. Ninety-seven of the examined isolates (47.78%) showed fractional inhibitory concentration (FIC) greater or equal to 2 (indicating antagonism). The synergistic activity of meropenem plus ertapenem combination suggests this combination can be a possible way to treat the infection caused by the carbapenem-resistant organisms, especially for IMP or NDM producer with a lesser minimum inhibitory concentration (MIC) and the infected individual who was not recommended to use colistin or tigecycline.